The treatment effect of posterior lumbar fusion surgery on patients suffering from lumbar disc herniation concurrent with peroneal nerve paralysis - Gao, Shangju; Li, Zhaohui; Li, Xiangyu; Rudd, Samuel; Wang, Haoming; Gao, Ze; Ding, Wenyuan; Yang, Sidong (Frontiers in Surgery, 2023)
Purpose: The purpose of this study is to investigate the clinical effect of posterior lumbar fusion surgery on patients who suffer from lumbar disc herniation concurrent with peroneal nerve paralysis. Methods: The patients suffering from peroneal nerve paralysis and undergoing posterior lumbar fusion surgery between January 2012 and December 2019 were retrospectively reviewed. The data of the identified patients were then collected and processed. All patients were followed up post-operatively after discharge from the hospital. The data was analyzed in terms of Oswestry disability index (ODI), visual analogue scale (VAS) score, and relative lower-limb muscle strength. Results: A total of 87 patients (52 males and 35 females) aged 54 ± 11 years met the inclusion criteria for this study. These patients stayed in hospital for 16 ± 6 days and were followed up for 81 ± 24 months. Data analysis showed that muscle strength of the tibialis anterior and extensor digitorum significantly recovered at the last follow-up with a grade of 3 (median), compared to grade 0 at admission (p<0.001). Furthermore, the median VAS score decreased to 1 at the last follow-up from 6 at admission (p<0.001), and the ODI greatly improved with 10% (median) at the last follow-up, while it was 58% at admission (p<0.001). The ODI improvement rate was 60% on average at the last follow-up. Multivariate regression analysis regarding the ODI and muscle strength improvement rates showed that advanced age was a risk factor for postoperative recovery. Conclusions: Most of the patients suffering from lumbar disc herniation concurrent with peroneal nerve paralysis can improve after undergoing posterior lumbar fusion surgery, but few can reach full recovery. Advanced age might be a risk factor that affects the prognosis of these patients after surgery.